Seismic Analysis and Comparison of Vertical Irregular Building Cases Using Response Spectrum Method - Abraham, Sipli; Kurian, Salini Theres N; Mani, Nissy Sussan; Aswathi, S; Ragav, Sreerenj (International Journal of Computer Sciences and Engineering, 2025)
Preliminary seismic risk assessment tools are used to screen existing buildings against potential seismic hazards. Buildings that perform poorly are prioritized for detailed evaluations to determine its condition. The risk of a building can be defined as the product of Hazard, Vulnerability, and Assets. Hazard is the earthquake itself. Vulnerability are building characteristics that make it more susceptible to the hazard. Assets are elements that add value to the structure such as building population. Vertical irregularities such as soft stories are considered in assessments but is much generalized. The National Structural Code of the Philippines (NSCP) defines soft story irregularities based on the reduction of stiffness in adjacent stories. Since the study is used for an ocular preliminary risk assessment of existing buildings, the soft story definition is simplified. In the study, it is assumed that the properties and number of structural members for each story is constant. Thus, soft stories may be defined by simply determining the height of the stories. The study is also limited to a single soft story at the first story. The severity of the soft story is varied by increasing the height of the soft story. A static pushover analysis is utilized to determine the performance of the building under different irregularity conditions. The output of the study may be used to improve existing level 1 seismic risk assessments. Due to the limitations of a static pushover analysis, the study only covers low-rise buildings as permitted by the NSCP. Though it is recognized that a dynamic time history is more suitable, a pushover analysis is sufficient due to the preliminary assessment nature of the objective. The study has found that one of the primary concerns in vertical irregularities is the localization of seismic demand. For soft story buildings, the concentration of seismic demand is where the soft story is located. Data from the pushover analysis is translated into score modifiers for the varying soft story severity which may be used for preliminary risk assessment tools.